A Robust Control Method for Damping and Tracking of Secondary Network Voltage of a PV Based Hybrid AC/DC Microgrid - Datta, Dristi; Fahim, Shahriar Rahman; Sarker, Subrata K.; Muyeen, S. M.; Islam Sheikh, Md. Rafiqul; Das, Sajal K. (Frontiers in Energy Research, 2020)
Future microgrids (MGs) will comprise of an enormous number of little secondary networks (SN) that will convey complex control for grid collaboration as well as tracking of operation. In this paper, a robust blended integral linear-quadratic-Gaussian (ILQG) controller is proposed for damping and tracking control of SN voltage of a PV based hybrid source of AC-DC microgrid against a number of operating conditions. The structure of this mixed controller is made by expanding the SN dynamics with the utilization of an integrator. The term SN signifies a network that can take power from the DC bus connected with the AC main grid and PV based DC grid. The aim of developing a DC bus is to provide the constant DC voltage in the SN load terminal which is made of a parallel combination of several uncertain and unknown loads that may produce the oscillation of its performance. The proposed blended integral linear-quadratic-Gaussian controller provides a large control bandwidth that not only reduces the oscillation but also confirms the improved tracking performance over the number of loads in SN premises. Additionally, several uncertainties are considered within the SN dynamics to check the robustness of the proposed blended controller. The evaluation of this blended controller is studied for the various load dynamics and compared with the linear-quadratic Gaussian (LQG), linear-quadratic-regulator (LQR), and integral controller (IC) in terms of settling time, bandwidth and tracking performances.